Respostas
respondido por:
0
Sendo uma equação do segundo grau definida por y=ax²+bx+c,temos:
x²-4x+5=0
Onde:
a=1 b=-4 c=5
E delta é:
Δ=b²-4ac=4²-4.1.5=16-20=-4
Então as raízes são:
(-b+ou-√Δ)/2a=[-(-4)+ou-√-4]/2.1=(4+ou-√4.√-1)/2=(4+ou-2.√-1)/2=2+ou-√-1
⇒ √-1=i
x'=2+i
x''=2-i
x²-4x+5=0
Onde:
a=1 b=-4 c=5
E delta é:
Δ=b²-4ac=4²-4.1.5=16-20=-4
Então as raízes são:
(-b+ou-√Δ)/2a=[-(-4)+ou-√-4]/2.1=(4+ou-√4.√-1)/2=(4+ou-2.√-1)/2=2+ou-√-1
⇒ √-1=i
x'=2+i
x''=2-i
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás